(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of ladder drill training on increasing the speed of Matra Pulsa Futsal Club players in Pasangkayu Regency. The research method used is a pre-experiment with a Group Pretest-Posttest Design. The sample in this study amounted to 12 players who were selected purposively. The instrument used is a 50-meter running test, conducted before and after the treatment of ladder drill training for 6 weeks, with a frequency of training four times a week. The results of data analysis using the t-test showed that there was a significant increase between the initial test results and the final test (tcount = 12.3732 > ttable = 2.201; p < 0.05). The average running time before training was 9.35 seconds, and after training decreased to 7.83 seconds. This study concludes that there is a significant effect of ladder drill training on the running speed of futsal players. This exercise is effectively used in training programs to improve physical abilities, especially the speed aspect in futsal games.